ANALISIS TINDAK TUTUR DIREKTIF DALAM PODCAST YOUTUBE RADITIYA DIKA EPISODE “DOKTER TIRTA SEKARANG BERUBAH” - Kusuma, Arum; Wahidy, Achmad; Effendi, Darwin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe certain implicatures in the speech delivered by Raditya Dika and Doctor Tirta in a conversation in a podcast broadcast on Raditya Dika's YouTube channel, in the episode entitled "Doctor Tirta Now Changed." In the conversation, Raditya Dika and Doctor Tirta discussed factors that influence health. This research is qualitative with a qualitative descriptive approach, which is based on Yule's theory (2014). Data collection was carried out through the listening and note-taking method, with data sources coming from Raditya Dika's YouTube Channel in the episode "Doctor Tirta Now Changed." The research findings show the presence of 41 data in the form of directive speech acts in the podcast